Characteristics of equestrian accidents and injuries leading to permanent medical impairment - Helena Stigson; Maria Klingegård (BMC, 2024)
Abstract Background Equestrian sports, also referred to as equestrianism, is practiced all over the world and a popular leisure activity in Sweden. Equestrianism is the country's second-largest youth sport, and previous studies indicate that accidents are common in equestrianism. However, few previous studies have examined acute equestrian injuries leading to permanent medical impairment (PMI). Methods By using nationwide insurance data comprising all injured equestrians registered in the Swedish Equestrian Federation, the aim was to analyse characteristics of equestrian accidents and particularly injuries leading to PMI, both in general and by age, gender, incident type, injury type and injured body region. Injury incidence and injuries leading to PMI were examined. All equestrians injured during 2017-2021 were included (n = 6,876), however, only injuries occurring in 2017 and 2018 were used to analyse the risk and the injury distribution of injuries leading to PMI. Injury incidence was calculated separately for males and females, as well as for different age groups, by dividing the number of insurance claims by the number of members multiplied by 1,000. Risk Ratio (RR) was calculated between gender. Pearson's chi-squared test was used to analyse differences in distribution for categorical variables. Results The majority of injuries affected females, correlating to approximately three times higher risk, compared to males. The age group 21-40 years were associated with the highest injury risk (14.26/1,000 registered riders). In total 12% of all injuries led to PMI. Injuries to the upper and lower extremities, along with fractures, had a higher risk of resulting in a PMI. The risk of injury leading to PMI was higher among riders over 20 years of age. Conclusions The fact that females face nearly three times the injury risk of males, and riders aged 21-40 had the highest injury risk while younger riders (Luke KL, McAdie T, Smith BP, Warren-Smith AK. New insights into ridden horse behaviour, horse welfare and horse-related safety. Appl Anim Behav Sci. 2022;246:105539.); (Havlik HS. Equestrian sport-related injuries: a review of current literature. Curr Sports Med Rep. 2010;9(5):299-302.); (Samuels K, Bettis A, Davenport DL, Bernard AC. Occupational vs. non-occupational equestrians: Differences in demographics and injury patterns. Injury. 2022;53(1):171-5.); (Gharooni A-A, Anwar F, Ramdeep R, Mee H. Severe equestrian injuries: A seven-year review of admissions to a UK major trauma centre. Trauma. 2023;25(1):41-7.); (Hasler RM, Gyssler L, Benneker L, Martinolli L, Schotzau A, Zimmermann H, et al. Protective and risk factors in amateur equestrians and description of injury patterns: A retrospective data analysis and a case - control survey. J Trauma Manag Outcomes. 2011;5:4.); (Meredith L, Brolin K, Ekman R, Thomson R. Analyses of injuries to equestrians in a Swedish district over a 16-year period. Translational Sports Med. 2019;2:270-8.) had a lower risk, indicates that preventive efforts should target both older and female riders. Injuries predominantly resulting in PMI involve upper and lower extremities, however, to prevent the most serious injuries significantly affecting a rider's daily life, measures preventing head and spinal cord neck injuries, must be implemented. Head injures remain the most frequent, serious and most significant group of injuries to prevent and mitigate, within equestrian sports.